Investigating multi-directional flow dynamics in three-way ball valves: a CFD-based study - Amol Dhumal; Nitin Ambhore; Gaurav Sanap; Tanmay Patil; Vishal Sanap; Aryan Kadu (Journal of Engineering and Applied Science)
Abstract The objective of this study is to analyze a three-way ball valve using computational fluid dynamic simulations in ANSYS Fluent to achieve better flow control and improve the efficiency of the system. The need to improve the energy efficiency and reliability of the fluid management system valves serves as motivation for this study. Flow analysis of the system includes determining key parameters like flow coefficient (C v ), pressure drop, and velocity distribution. A structured hexahedral mesh with layers of inflation was used to better capture flow behavior along with a grid independence check to ensure the right balance between accuracy and computation cost. Simulations were performed under five boundary conditions: velocity inlet and pressure outlets for the wall and volume to be treated as stationary. Complex interactions within the flow are prominent as significant differences in velocity as well as pressure occur at the junction of the valve. The valve characteristics were defined using C v calculated at different velocities and various positions of the opening of the valve non-linearly correlated to the characteristics. Restrictive path effect on system pressure drop was measured in open and closed paths to assess the impact of restriction features on valve performance. The effects of the dynamic forces of control systems on valve positioning and flow regulation are pointed out as elucidated by the results of management of fluid forces during valve control. This research contributes towards the development of efficient and reliable three-way ball valves, which help in advancements in industrial fluid control systems.